Demonstration Methods to Improve Students' Learning Outcomes in Class 2 Pancasila Symbol Materials at SD N Utan Kayu Selatan 01 2022/2023 - Paulus , Kristo; Simatupang , Sondang Elfrida; Darma, Rio Sadhika (Sinergi International Journal of Education, 2023)
There are many ways to improve learning outcomes, where one of the methods used is the demonstration method, if most of the teaching material is only delivered in verbal language so that it is sometimes difficult for students to understand, then with the demonstration method the explanation becomes easier for students to understand. The method used is qualitative with a class action model. The aim of the study was to determine the effect of the demonstration method on the learning outcomes of Civics class 2 students at SDN Utan Kayu Selatan 01 Jakarta for the 2022/2023 academic year. This research is a two-round action research with each cycle consisting of four stages, namely planning, action and observation, reflection, and review. The subjects of this study were grade 2 students at SD N Utan Kayu Selatan 01 Jakarta for the 2022/2023 academic year whose student learning outcomes increased from Cycle I to Cycle II. Cycle I (51%) and Cycle II (89%). This study found that the demonstration method had a good effect on student learning outcomes at SD N Utan Kayu Selatan 01 East Jakarta and this learning method could be used as an alternative to civics learning.